Correction: Large-scale electricity storage utilizing reversible solid oxide cells combined with underground storage of CO2 and CH4. Issue 2 (25th November 2016) - Jensen, S. H.; Graves, C.; Mogensen, M.; Wendel, C.; Braun, R.; Hughes, G.; Gao, Z.; Barnett, S. A.
Abstract : Correction for 'Large-scale electricity storage utilizing reversible solid oxide cells combined with underground storage of CO2 and CH4 ' by S. H. Jensen et al., Energy Environ. Sci., 2015, 8, 2471–2479.